Analysis of the spatial relationship between small olive farms to increase their competitiveness through cooperation. (April 2017) - Colombo, S.; Perujo-Villanueva, M.
Highlights: The great majority of traditional olive farms are small and barely profitable. Maintaining small agricultural farming is socially desirable given the social and environmental services they provide. Farmers' cooperation can be a valuable option to increase the profitability of small agricultural holdings. Spatial relationships between small farms and between small and large farms must be taken into account to foster cooperation. Policies aiming at incentivising farmers' cooperation should differ depending on whether assisted or shared cooperation is desired. Abstract: Small olive farms typically find it hard to compete with their larger competitors due to unfavourable conditions in terms of labour costs, land fragmentation and structural capital. These conditions result in higher production costs that reduce their competitiveness, leading to progressive exclusion from domestic and international markets and the abandonment of farming. In this scenario, cooperation between farmers to increase farm size and reduce land fragmentation may be an innovative strategy to improve the competitiveness of small agricultural holdings and avoid farm abandonment. The aim of this paper is to characterize the spatial structure of the traditional olive grove in the province of Jaén (South of Spain), the world's leading olive oil producer, to identify the areas where farmer cooperation can be effectively implemented. The results of this study confirm that there are large numbers of small, barely viable olive groves and show different ways to promote cooperation between farmers according to the structural characteristics of their farms and their spatial relationships. In particular, when small olive farms have large neighbours, assisted cooperation systems should be implemented, while when small olive farms are concentrated in areas without larger farms, shared cultivation systems would be more efficient. This paper also provides information for the design of public policies aimed at enhancing the competitiveness of small agricultural holdings.